Корелација између суперрекомбинантне когнитивне дисфункције и флуктуације нивоа фактора раста фибробласта 21 (ФГФ21): Cognitive dysfunction and fluctuations in serum FGF21) - Lyu, Guotian; Lu, Xiaoli; Meng, Qi-Chang; Liu, Yanyan; Liu, Shuyan; Liu, Jieyi; Dong, Peng (Journal of Medical Biochemistry, 2025)
Objective: To explore the changing characteristics of cognitive function in overweight/obese (OWO) adolescents and analyze its relationship with the level of serum fibroblast growth factor 21 (FGF21).Methods: A total of 175 adolescents were selected and divided into a normal body mass index (BMI) group (n=50), an overweight BMI group (n=50), and an obese BMI group (n=75). All participants underwent assessment of anthropometric indicators (height, weight, waist circumference, BMI Z score). Fasting venous blood was collected to measure the level of serum FGF21 (by enzyme-linked immunosorbent assay (ELISA)), as were metabolic parameters such as fasting plasma glucose (FPG), fasting insulin (FINS), glycated hemoglobin (HbA1c), and lipid profiles (TC, TG, LDL-C, HDL-C). Overall cognitive function was evaluated via the Chinese version of the Montreal Cognitive Assessment Foundation Scale (MoCA-B), executive function was evaluated via the Wisconsin Card Sorting Test (WCST) (with a focus on analyzing the number of persistent errors/PE and the number of completed classifications/CC), and working memory was evaluated via the number span test (DST). Independent sample t tests or Mann‒Whitney U tests were used to compare the differences between groups. Pearson or Spearman correlation analysis was used to explore the relationships between serum FGF21 levels and cognitive indicators and metabolic parameters. Multiple linear regression was used to analyze the independent association between serum FGF21 and cognitive function scores (after adjusting for potential confounding factors such as age, sex, BMI Z Score, and HOMA-IR).Results: Compared with those of the normal individuals, the systolic blood pressure, diastolic blood pressure, fasting blood glucose, glycated hemoglobin and triglyceride levels of the adolescents in the obese group were greater (all P